Crystal structure refinement and the magnetic and electro-optical properties of Er3+–Mn2+-substituted Y-type barium hexaferrites. Issue 13 (1st July 2021) - Mohammed, J.; Batoo, Khalid Mujasam; Abdulaziz, A.S.; Safana, A.S.; Hafeez, H.Y.; Raslan, Emad H.; Hadi, Muhammad; Assiafan, AbdulAziz K.; Imran, Ahamad; Srivastava, A.K.
Abstract: The influence of Er 3+ –Mn 2+ substitution on the properties of Y-type hexaferrites (chemical composition: Ba2–x Erx Zn0.6 Co0.6 Cu0.8 Fe12−y Mny O22 (x = 0.0, 0.3, and 0.5 and y = 0.0, 0.4, and 0.6)), which were synthesized by the sol-gel autocombustion method, was investigated. The X-ray diffraction spectra were analyzed by the Rietveld refinement method, and hexaferrite was observed to possess a single-phase crystalline structure, whereas the Fourier-transform infrared spectra clarified the formation of the iron oxide base material. The morphology of the grains revealed that they were hexagonal and without agglomeration. The band gap of the samples decreased as the Er 3+ –Mn 2+ concentration increased. Dielectric and impedance spectroscopies of the prepared samples indicated the role of polarization in the variation in the dielectric and impedance parameters. Particularly, the occurrence of space-charge polarization increased the dielectric constant at lower frequencies. Further, the Cole–Cole plot revealed a semicircle in the lower frequency region, thereby indicating that the grain boundary contributed the most to the dielectric constants. Modulus spectroscopy revealed that the charge mobility increased as the concentration of Er 3+ –Mn 2+ increased. Additionally, the magnetic analysis indicated that Mn 2+ preferably replaces Fe 3+ at the octahedral site, thereby reducing the magnetization of the prepared samples through a reduced superexchange interaction. Furthermore, increasing the coercivity values thermally stabilized the sample, and this is vital for perpendicular magnetic recording.